Investigation and Numerical Simulation of Different Piezoelectric Bimorph Cantilever Designs for Energy Harvesting - Khan, Aimal; Nawaz, Muhammad Qasim; Xu, Lu (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2024)
The study investigates the dynamic performance and energy harvesting efficiency of different cantilever configurations using numerical simulations. It examines factors such as material properties, geometrical parameters, and excitation conditions to optimize the design for enhanced energy harvesting capabilities. The research contributes to understanding how different cantilever designs affect the overall performance and efficiency of piezoelectric energy harvesters. Vibrational energy harvesters, also known as MEMS, have become popular due to their efficiency and ease of inclusion in microsystems. COMSOL Multiphysics was used to simulate six different forms of piezoelectric bimorph cantilevers for energy harvesting. Designs were analyzed, with each design having a distinct arrangement of proof masses. Design 01 had a rectangular cantilever with a proof mass connected to its top surface, Design 02 used a rectangular cantilever, Design 03 used a novel approach, Design 04 used a trapezoidal cantilever, and Design 05 preserved the trapezoidal form but moved the proof mass to the structure's base. Design 06 successfully completed the trapezoidal cantilever. The study found that design 04 had a significant advantage in power production efficiency at higher resistor values, surpassing design 01 in power output. The use of these varied designs allows for an exhaustive examination of piezoelectric bimorph cantilever configurations, potentially leading to insights that may enhance energy harvesting effectiveness in various applications.